Alcohol Consumption and Risk of Parkinson's Disease: Data From a Large Prospective European Cohort. Issue 7 (1st May 2020) - Peters, Susan; Gallo, Valentina; Vineis, Paolo; Middleton, Lefkos T.; Forsgren, Lars; Sacerdote, Carlotta; Sieri, Sabina; Kyrozis, Andreas; Chirlaque, María‐Dolores; Zamora‐Ros, Raul; Hansson, Oskar; Petersson, Jesper; et al.
Abstract: Background: Parkinson's disease (PD) etiology is not well understood. Reported inverse associations with smoking and coffee consumption prompted the investigation of alcohol consumption as a risk factor, for which evidence is inconclusive. Objective: To assess the associations between alcohol consumption and PD risk. Methods: Within NeuroEPIC4PD, a prospective European population‐based cohort, 694 incident PD cases were ascertained from 209, 998 PD‐free participants. Average alcohol consumption at different time points was self‐reported at recruitment. Cox regression hazard ratios were estimated for alcohol consumption and PD occurrence. Results: No associations between baseline or lifetime total alcohol consumption and PD risk were observed. Men with moderate lifetime consumption (5–29.9 g/day) were at ~50% higher risk compared with light consumption (0.1–4.9 g/day), but no linear exposure–response trend was observed. Analyses by beverage type also revealed no associations with PD. Conclusion: Our data reinforce previous findings from prospective studies showing no association between alcohol consumption and PD risk. © 2020 The Authors. Movement Disorders published by Wiley Periodicals, Inc. on behalf of International Parkinson and Movement Disorder Society.